Attitudes of Indonesian Mothers towards Children’s Advertising for Food - Lanasier, Evi (Routledge, 2014)
Advertising directed toward children is a controversial issue with growing concerns from parents around the world, including emerging markets such as Indonesia. The reasons for its negative effects include that such advertising could lead to materialism, parent–child conflict, and feelings of unhappiness. In particular, advertising by food companies is a target for criticism due to concerns about unhealthy food and childhood obesity. This article reports on the findings of a number of focus groups of Indonesian mothers to obtain an indication of the mothers’ ethical judgment toward such advertising. The results identify reasons why the mothers found particular advertisements to be unethical and ways advertisements can improve their message. From the responses, some important issues are raised that would be of interest to international advertisers.